2018
DOI: 10.1016/j.conbuildmat.2018.02.157
|View full text |Cite
|
Sign up to set email alerts
|

Fracture studies on synthetic fiber reinforced cellular concrete using acoustic emission technique

Abstract: Cellular lightweight concrete (CLC) is increasingly used for low strength non-structural and structural applications. The effects of synthetic fiber reinforcement on the fracture behavior of CLC is investigated. In particular, acoustic emission (AE) technique is employed to study the influence of macro (structural), micro polyolefin synthetic fibers and their combinations on the fracture behavior of CLC beams. Notched fiber reinforced CLC beams were tested to study the crack initiation and propagation characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…With advantageous properties like low specific density, energy absorbing, low thermal conductivity, and high acoustic insulation, lightweight foamed cement-based composites are increasingly used in various low strength structural and nonstructural applications (Rasheed et al., 2018). The foamed cement-based material is such a lightweight porous material which is prepared by chemical or physical foaming procedure (Krämer et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With advantageous properties like low specific density, energy absorbing, low thermal conductivity, and high acoustic insulation, lightweight foamed cement-based composites are increasingly used in various low strength structural and nonstructural applications (Rasheed et al., 2018). The foamed cement-based material is such a lightweight porous material which is prepared by chemical or physical foaming procedure (Krämer et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As extensively studied, the cementitious composites were quasi-brittle materials with brittle matrix and low strain capacity (Zhang et al., 2013). Short and randomly distributed fibers normally are used to improve the brittleness and poor resistance of crack initiation and propagation of composites (Park et al., 2017; Rasheed et al., 2018). The incorporation of fibers as the reinforcement in foamed cement-based composites is also proved an effective method to improve the mechanical strength and ductile properties (Rasheed et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carpinteri et al evaluated the damage localisation of strengthened walls using AE technology and predicted the time to failure in fatigue tests. Rasheed et al employed an AE technique to study the influence of different polyolefin synthetic fibres and their combinations on the fracture behaviour of cellular lightweight concrete beams, and results indicated that the crack sources located by the technique were consistent with the actual crack development. Wang et al applied an AE analysis method to monitor the damage evolution of ultra‐high performance concrete (UHPC) specimens subjected to direct tension and concluded that the method provided great insight into the multiple cracking behaviour of UHPC during the strain‐hardening stage.…”
Section: Introductionmentioning
confidence: 99%